Local Governments and Public Politics of Education of Youths and Adults - Elmir de Almeida; Marilena Nakano; Marli Pinto Ancassuerd (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This article objectives to present and to analyze the manners as governments of local administrations of urban space, in recent years, come drawing and implementing public politics of youths' and adults' education. First, it is approached the public politics of youths' and adults' education implemented by city Executives, between 1987-2003. Period during which we can verify, in the Area that served as scenery to the study, the emergency and coexistence of two "generations of politics": the first anchored in the idea of supplying State and the second anchored in the principle of the social participation and marked by the evident shortage of resources. It was looked for, still, to analyze the place that the executed public actions occupied inside the organization of the school education and the contribution that it gave to guarantee the social participation and the new actors' constitution in the public sphere.